Study of blood pressure to height ratio and its relation with standard BP percentile charts to detect the prehypertension in age group 12 to 15 yrs - Dr. A B Kurane; Dr. Mrs. I A Kurane; Dr. N S Magdum; Dr. S Sumana (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: The prevalence of adolescent (pre) hypertension, even in developing countries, is rising steeply, probably due to urbanization and the positive energy balance – typified by excess weight gain – that comes with it. Primary prevention of one of the leading health problems, i.e. hypertension and ischemic heart disease in adults necessitates a scientific evaluation of the predictors in children. Currently, blood pressure percentile in childhood is assessed according to age, gender, height.Aim & Objectives: To study blood pressure to height ratio and its relation with standard BP percentile charts to detect (pre) hypertension.Methodology: BP percentile was calculated for 2000 adolescents. Receiver operating characteristic (ROC) curve analyses were performed to calculate sensitivity and specificity of BP/height ratios as diagnostic tests for elevated BP (90%). Correlation analysis was performed between BP percentile and BP/height ratios.Result: In our study average age was 13.1 ± 1.2 years. SBP/height ratio was ≥0.7607 and ≥0.7795 in boys and girls respectively. And DBP/height ratio was ≥0.4513 and ≥0.46 in boys and girls respectively. The ratios strongly correlate with the BP percentile charts with high sensitivity and specificity.Conclusion: The BP/height ratios correlate with the corresponding standard BP percentiles charts in both genders. It may eliminate the under-diagnosis of adolescent (pre)hypertension and hypertension, and in turn, may help to reduce morbidity and mortality resulting from its sequelae.